A Biochemical Study on Lead Effect Upon Oil Refinery Workers - R. Hasan, Hathama; M. Dahham, Zainab (Asian Journal of Chemistry, 2012)
This study dealt on 40 males workers at Doura refinery oil in Baghdad city of Iraq in order to check the effect of using tetra ethyl lead on human health. The study involved as well (30) age matched healthy individuals to be used as control group. The measured parameters were:- blood lead level, Hb concentration, total serum protein's concentration and ceruloplasmin (ferroxidase; iron(II):O2 oxidoreductase, EC 1.16.3.1) ferroxidase activity. The workers group was divided into two subgroups according to their blood lead level: subgroup A (10-19 μg/dL) and subgroup B (19-42 μg/dL). The results indicated presence of an increase in blood lead level and a decrease in hemoglobin concentration in the workers subgroups in comparison with that of control group (p < 0.05). While a non significant differences were observed in the concentration of total serum protein among the studied groups (p < 0.05). Moreover upon the comparison of cp ferroxidase activity and specific activity between the workers groups and control groups, a non significant decrease in the workers subgroup A (p < 0.05), but a significant decrease was noticed in the workers subgroup B (p < 0.05).